2003
DOI: 10.3758/bf03194389
|View full text |Cite
|
Sign up to set email alerts
|

Incidental formation of episodic associations: The importance of sentential context

Abstract: The influence of relevant semantic context on the incidental formation of episodic associations between words was probed in two experiments. In Experiment 1, we examined the influence of associations formed incidentally between unrelated words presented either in isolation or embedded in a sentential context on subsequent explicit paired-associate learning tested by cued recall. The results of Experiment 1 showed that the cued-recall rate of words studied in sentential context was higher than that of words co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…In particular, under conditions of an incongruent relationship between sponsor and event, articulation of the reasons for tbe sponsorship relationship resulted in improved recall for the relationship. These results are in accordance with recent research in psychology by Prior and Bentin (2003) that showed that incidental learning of the pairing of two unrelated nouns was better when they were linked in a meaningful sentence than when presented in isolation.…”
Section: Articulationsupporting
confidence: 82%
“…In particular, under conditions of an incongruent relationship between sponsor and event, articulation of the reasons for tbe sponsorship relationship resulted in improved recall for the relationship. These results are in accordance with recent research in psychology by Prior and Bentin (2003) that showed that incidental learning of the pairing of two unrelated nouns was better when they were linked in a meaningful sentence than when presented in isolation.…”
Section: Articulationsupporting
confidence: 82%
“…Prior and Bentin (2003) found that pairs of words can be better remembered if embedded in sentences than if presented on their own at encoding; this facilitation effect of sentence context does not hold for memory for individual words. Furthermore, it seems to be specific to situations in which the sentence that includes the word pair is meaningful and can be fully integrated at the semantic level (Prior and Bentin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Unitization refers to the creation of a novel entity that is "more than the sum of its parts", just as a word is more than a collection of letters or a painting more than a collection of brushstrokes, a topic often studied in Gestalt psychology (Wagemans et al, 2012a,b) as well as in the study of the perception of both simple and complex stimuli (Townsend & Wenger, 2015). The formation of unitized representations may be encouraged by semantic elaboration of either word pairs (Graf & Schacter, 1985;Prior & Bentin, 2003, 2008 or image pairs (Kan et al, 2011), resulting in the storage of stronger associative information. As in the present study, repetition of intact word pairs has been found to enhance memory for their association beyond any benefit from repeating the component items (Kilb & Naveh-Benjamin, 2011;Parks & Yonelinas, 2015), suggesting that associative information is a unitized representation of the complete pair that can be strengthened separately from representations of items.…”
Section: What Is Associative Information?mentioning
confidence: 99%